Advanced glycation endproducts link inflammatory cues to upregulation of galectin-1 in diabetic retinopathy. Issue 1 (December 2017) - Kanda, Atsuhiro; Dong, Yoko; Noda, Kousuke; Saito, Wataru; Ishida, Susumu
Abstract Diabetic retinopathy (DR) is an inflammatory and progressive vaso-occlusive disease resulting in angiogenesis. Galectin-1 is a hypoxia-induced angiogenic factor associated with cancer and proliferative DR. Here we reveal a significant upregulation of galectin-1 in eyes of DR patients along with progression of clinical stages beginning from the pre-ischemic, inflammatory stage with diabetic macular edema, but not in eyes with non-diabetic retinal vascular occlusions. As for its regulatory mechanism unrelated to hypoxia but selective to DR, in vitro galectin-1/LGALS1 expression was shown to increase after application to Müller glial cells with interleukin (IL)-1β, which was induced in monocyte-derived macrophages and microglial cells via toll-like receptor (TLR) 4 signaling stimulated by advanced glycation endproducts (AGE).In vivo inhibition of AGE generation with aminoguanidine, macrophage depletion with clodronate liposomes, and antibody-based blockade of Il-1β and Tlr4 attenuated diabetes-induced retinalLgals1 expression in mice. Fibrovascular tissues from proliferative DR eyes were immunoreactive for AGE, TRL4 and IL-1β in macrophages, and IL-1β receptor-positive glial cells expressed galectin-1. Therefore, diabetes-induced retinal AGE accumulation was suggested to activate IL-1β-related inflammatory cues in macrophages followed by Müller cells, linking to galectin-1 upregulation in human DR with time. Our data highlight AGE-triggered inflammation as the DR-selective inducer of galectin-1.